PENGARUH MODEL DISCOVERY LEARNING DISERTAI MEDIAGAMBAR TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMK NEGERI 1 RAMBAH TAHUN PEMBELAJARAN 2015/2016 - -, Yuhernis (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The purpose of this research was to determine whether or not the effect of  discovery learning model with picture media on learning outcomes of biology grade X SMK 1 Rambah acadimic year 2015/2016. This research is quasi-experimental. The sample in this study were students of grade X MP ( mechanization of agriculture) and grade X TPHP (agro-processing technique). The results showed that the material of mushroomin biology using discovery learning model with picture media was better than learning without using discovery learning model picture media assisted learning. It can be see from the average value of the experimental class has an average value of  80, while the  average value of the control class was 67.14. it can be concluded that there was the influence of discovery learning model with picture media on learning outcomes biology grade X SMK 1 Rambah in academic 2015/2016. .